KONFLIK AGRARIA DALAM PEMBANGUNAN IBU KOTA NEGARA: ANALISIS HAK GUNA USAHA DAN PERLINDUNGAN HAK MASYARAKAT ADAT - Kurniawan, Fahmi (Smart Education, 2025)
Abstract: The relocation of the National Capital City (IKN) from Jakarta to East Kalimantan presents major challenges, particularly in relation to customary land rights and Cultivation Rights (HGU). Indigenous communities in the region have deep historical and cultural connections to the land, but often lack formal proof of ownership of their land. This increases the potential for conflict when customary land is allocated for the development of IKN, which is regulated in the IKN 2023 Law. This law allows investors to extend the HGU for up to 190 years, a policy that contradicts the agrarian principles in the 1960 BAL, which emphasise equitable land distribution and the protection of indigenous peoples' rights. From an agrarian law perspective, granting such lengthy HGU licences to investors could undermine the rights of indigenous peoples who have long inhabited the area. Indigenous peoples also face legal uncertainty over land that has been part of their lives and culture for centuries. This study highlights the importance of agrarian regulations that protect the rights of indigenous peoples while supporting the investment and development needs of IKN. The government needs to align its IKN policy with the protection of indigenous peoples' rights through a fair and inclusive legal approach. This policy will ensure sustainable development without ignoring the traditional rights of local communities. Keywords: Agrarian Conflict, Cultivation Rights Title (HGU), Legal Certainty. Abstrak: Pemindahan Ibu Kota Negara (IKN) dari Jakarta ke Kalimantan Timur menghadirkan tantangan besar, terutama terkait dengan hak tanah adat dan Hak Guna Usaha (HGU). Masyarakat adat di wilayah tersebut memiliki hubungan historis dan budaya yang mendalam dengan tanah tersebut, namun sering kali tidak memiliki bukti kepemilikan formal atas tanah mereka. Hal ini meningkatkan potensi terjadinya konflik ketika tanah adat dialokasikan untuk pembangunan IKN, yang diatur dalam Undang-Undang IKN 2023. UU ini memberi izin perpanjangan HGU hingga 190 tahun bagi investor, suatu kebijakan yang bertentangan dengan prinsip agraria dalam UUPA 1960, yang menekankan distribusi tanah yang adil dan perlindungan hak masyarakat adat. Dalam perspektif hukum agraria, pemberian HGU yang begitu panjang kepada investor dapat mengabaikan hak-hak masyarakat adat yang sudah lama mendiami wilayah tersebut. Masyarakat adat pun menghadapi ketidakpastian hukum atas tanah yang telah menjadi bagian dari kehidupan dan budaya mereka selama berabad-abad. Studi ini menyoroti pentingnya regulasi agraria yang mampu melindungi hak-hak masyarakat adat sembari mendukung kebutuhan investasi dan pembangunan IKN. Pemerintah perlu menyelaraskan kebijakan IKN dengan perlindungan hak-hak masyarakat adat melalui pendekatan hukum yang adil dan inklusif. Kebijakan ini akan memastikan pembangunan yang berkelanjutan tanpa mengabaikan hak-hak tradisional masyarakat lokal. Kata kunci: Hak Guna Usaha (HGU), Konflik Agraria, Kepastian Hukum.